1989
DOI: 10.1161/01.str.20.5.691
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous calcific cerebral embolus from a calcific aortic stenosis in a middle cerebral artery infarct.

Abstract: Calcific emboli from a calcific aortic stenosis is an uncommon eventA 73-year-old right-handed man had the sudden onset of aphasia and right hemiparesis. He had been treated for hypertension over the previous 10 years. One year earlier, a pulsed Doppler echocardiogram carried out for effort-related cardiac symptoms of angina pectoris, dyspnea, and syncope showed moderately tight CAS. An aortic outlet of approximately 1 cm 2 , with minimal aortic insufficiency and left ventricular hypertrophy, was demonstrated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
3

Year Published

1990
1990
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 8 publications
0
21
0
3
Order By: Relevance
“…In spite of these findings, we found 5 published cases of documented cerebral SCE from the aortic valve [1, 7, 8, 9, 10]. One could argue that most of these strokes were not due to real SCE, but to microthrombi originating from a calcified valve; alternatively, it has been suggested that CAS could be a marker of a generalized atherosclerotic process in patients with concomitant multiple risk factors [6].…”
Section: Discussionmentioning
confidence: 96%
“…In spite of these findings, we found 5 published cases of documented cerebral SCE from the aortic valve [1, 7, 8, 9, 10]. One could argue that most of these strokes were not due to real SCE, but to microthrombi originating from a calcified valve; alternatively, it has been suggested that CAS could be a marker of a generalized atherosclerotic process in patients with concomitant multiple risk factors [6].…”
Section: Discussionmentioning
confidence: 96%
“…- 82 Calcium deposition in the aortic valve may be visible by fluoroscopy or chest roentgenogram. The electrocardiogram may show left bundle branch block or advanced atrioventricular block with extensive aortic calcification.…”
mentioning
confidence: 99%
“…These risk factors are similar to those of ischemic stroke [14,15,16]. Case reports separately provide evidence of brain infarction due to calcific emboli from aortic valves [17,18,19,20,21,22,23]. However, several previous studies have suggested that there is no association between aortic VaT and cerebrovascular events [24, 25].…”
Section: Discussionmentioning
confidence: 85%